Nephrotoxic effects of aminoglycosides on the developing kidney - Samira Samiee-Zafarghandy; Johannes N. van den Anker (Hygeia Press di Corridori Marinella, 2013)
Aminoglycosides are the most commonly used antibiotics in infants hospitalized in neonatal intensive care units. Despite their outstanding efficacy profile, aminoglycosides remain relatively toxic with a narrow therapeutic index and a potential to cause nephrotoxicity and/or ototoxicity. Although aminoglycoside-induced nephrotoxicity has been the subject of multiple studies, the short- and long-term effect of aminoglycosides administration on the developing kidney of the fetus or premature newborn has not yet been determined. In this review the currently available evidence about the effects of aminoglycosides on the developing kidney and the mechanisms involved in aminoglycoside-induced nephrotoxicity are presented.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research